From treaty-making to treaty-breaking models for ASEAN external trade agreements - Kuijper, Pieter Jan; Mathis, James H.; Morris-Sharma, Natalie Y. (Integration through law : the role of law and the rule of law in ASEAN integration, 2015)
"This book comprising the ten member states of Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Viet Nam, has undertaken intensified integration into the ASEAN Community through the Rule of Law and Institutions in its 2007 Charter"--Provided by publisher.